Healthy Mobilities. Issue 2 (1st June 2021) - Bell, Sarah L.; Cook, Simon
Abstract: In this article, we articulate a distinct conceptual direction at the intersection of health and mobilities scholarship that centers on healthy mobilities. We take inspiration from relational, multiscalar, and more-than-human approaches to foreground an approach that asks what being in everyday healthy motion may entail and whose health is considered. We trace this approach through two brief provocations: exercise and differential mobilities, including the finely tuned movement-repertoires developed by disabled people. These illustrate the value of healthy mobilities, beyond humancentric, cure-oriented approaches to health, to understandings of how health takes shape among diverse living entities in motion. This focus can help foreground the interdependence of human, nonhuman, and planetary health in mobilities.